ANALISIS POTENSI PEMANENAN AIR HUJAN UNTUK PEMENUHAN KEBUTUHAN AIR BERSIH DI NEGERI PASSO BENTENG KARANG KECAMATAN BAGUALA, KOTA AMBON - Dewi Cantika Putri; Warniyati Warniyati; Monica R. Tutkey; Tri O. Sihombing (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Negeri Passo Benteng Karang, a hamlet in Baguala Sub-district, is located in a hilly area with rocky soil, making it challenging to access groundwater sources. Despite having one borehole and a single reservoir, the community frequently faces clean water shortages, as the current supply is insufficient for daily needs. To address this issue, a cost-effective and efficient solution, namely rooftop rainwater harvesting (RWH), is proposed. This study analyzes climate, rainfall using the Gumbel method, community water demand, planned discharge using the rational method, and the potential of RWH. The results indicate a maximum harvestable water volume of 4,133.5 m³/day with rainfall exceeding 100 mm, while the clean water demand is 144 m³/day. Thus, the clean water needs of Negeri Passo Benteng Karang can be fully met through the implementation of the RWH method. Keywords: Clean Water, Rainfall, Rainwater Harvesting